Pengaruh pelatihan penjamah makanan tentang sistem pengolahan dan penyajian makanan terhadap mutu makanan pasien di RSUD Prof. Dr. Margono Soekarjo Purwokerto - Nurrekta Yuristrianti; Tjahjono Kuntjoro; Toto Castro (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2007)
Background: Special attempts should be done to improve patient’s food quality. One of them is by choosing skillful and professional staff in the food processing and service according to the standard. Patient’s food service unit in Margono Soekarjo Hospital, Purwokerto applying catering system that in its policy should consider some factors including training and educational program.Objective: To find out the effect of training on food handler and service system for staff dealing with food on patient’s food quality improvement in Margono Soekarjo Hospital, Purwokerto.Method: This was a quasi experimental study with a timeseries approach. The subjects were 30 staff of food handler and patients in class-II and class-III for more than 2 days and got regular diit. Data were collected through observation and evaluation using questionnaires and visiting records. Evaluation was done on knowledge, attitude, and skills of the staff of food handler; on patient’s food quality and patient’s satisfaction with food quality. Data were analyzed using t-test and anova.Results: Training affected improvement on knowledge, attitude, and skills of staff food handler. The evaluation of food quality after training showed improvement in the aspects of performance and taste of all kinds of food with good grade in average. Meanwhile the evaluation of patient’s satisfaction after training showed stability in the observation 01 (month 1), 02 (month 2) and 03 (month 3) with satisfaction grade in average. Observation on patient’s food waste showed that in average the food that was not consumed by patients was <25%.Conclusion: Training on food serving and processing system affected improvement of knowledge, attitude, and skills of the staff of food handler; food quality, and patient’s satisfaction with food quality.